Efektivitas Suhu Perendaman Nanas dan Jeruk Nipis terhadap Penurunan Kadar Formalin dalam Ikan Asin Teri Nasi - Amelia Handayani Burhan (Politeknik Kesehatan Bhakti Setya Indonesia, 2021)
Anchovy salted fish are in great demand by the public. Unfortunately, in recent years, anchovy salted fish containing formalin have been found. Various efforts have been made to reduce the amount of formalin that may be consumed when people process anchovies and anchovies, including using ingredients that contain acids, such as pineapple and lime. In addition to the addition of acid compounds, formalin can also be removed by applying heat. Based on these two things, this study aims to find out the effectiveness or influence of the immersion temperature of pineapple and lime juice on the level of formalin present in anchovies and anchovies. The research design is Posttest Only Control Design. Samples of anchovy salted fish were obtained from 5 traditional markets in the city of Yogyakarta by random sampling method. The identification of formalin in the sample was tested using the ET Group brand formalin test kit. The positive samples were then treated with pineapple and lime juice immersion at temperatures of 30, 45, 60, 75 and 90°C for 30 minutes, respectively. Formalin levels before and after treatment were determined by acidimetric method using HCl solution and methyl red indicator. Furthermore, the research data were tested statistically. The results of the qualitative test found that all positive samples contained formalin. The level of formalin in the sample before treatment was 0.939% (w/w). Soaking anchovies and anchovies with pineapple and lime juice at various temperatures was proven to be effective in reducing formalin levels (Sig<0.05). The higher the temperature, the more formalin is successfully removed. At a temperature of 90°C, pineapple juice was able to reduce formalin levels up to 51% while lime juice was able to reduce formalin levels up to 71%.